PEMASARAN INFLUENCER DAN IDENTITAS DIGITAL: EKSPLORASI ANTROPOLOGIS BUDAYA KONSUMEN ONLINE - Djufri, Djufri (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This study explores how influencer marketing shapes digital identity and spatial relations in Makassar, Indonesia, through a spatially grounded urban ethnography approach. This framework enables a deep reading of how urban residents engage with digital practices to navigate symbolic and spatial exclusion generated by influencer content. Through social media observation, narrative interviews, and the tracing of urban locations featured in visual representation, the study finds that influencer marketing does not merely sell products—it also reproduces social hierarchies through aesthetic spatiality and the logic of visibility. Yet, amid such exclusions, marginalized communities deploy diverse tactics of resistance, including visual reengineering, the use of alternative locations, and digital irony that disrupt dominant narratives. These findings suggest that digital identity is not passively consumed but actively negotiated through concrete and often unexpected spatial relations. Drawing on Lefebvre’s theory of the production of space, Urry’s concept of digital mobilities, and Gandy’s politics of infrastructure, the study shows how cities and digital spaces co-constitute a contested symbolic terrain. The article’s main contribution lies in advancing a Global South perspective, where digital technologies and aesthetics are practiced contextually and do not always conform to the logics of global capitalism. This research underscores that urban—and digital—space is not solely produced from above, but also from below, through the everyday agency of ordinary citizens.